On determining frost susceptibility of soils - Saarelainen С. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
Freezing and thawing of soils are common in cold regions. They may even be considered as limit states from the thermo-hydro-mechanical point of view. Thus, to characterize the behavior of freezing and thawing soils, some basic principles should be considered. Design to prevent frost damage should be based on theories that have been shown to apply to field conditions. The laboratory procedures used in the design should imitate the expected freezing behavior, and the tested specimen should be prepared to simulate the soil conditions in the field. The parameters from the test should be applicable to the design model. If these principles are not applied, then the frost susceptibility can be considered as a limit classification property describing the risk of damage in freezing and thawing.